Conversações, brincadeiras e andanças com as crianças: um estudo a partir da “gramática das culturas da infância” - Matta, Yamilli Karen Rodrigues de Pinho da (2021)
In order to understand the social position that contemporaneity has reserved for children and, above all, the interest in the place that children build through their cultures, Sarmento (2003a) points to the existence of a grammar which is proper to children’s cultures. This grammar deals with a symbolic normativity, expressed by the dimensions of semantics, syntax and morphology, which considers the interactivity, the playfulness, the fantasy of reality and reiteration as structuring axes of children’s cultures. Based on the theoretical reflections proposed by Sarmento (2003a) on the grammar of children’s cultures and in dialogue with the contributions of historiography of childhood (ARIÈS, 1986), sociology of childhood (SARMENTO, 2003a; 2003b; CORSARO, 2011), anthropology of childhood (COHN, 2005) and geography of childhood (LOPES, 2018), this study aims to investigate how the grammar of children’s cultures reveals the social position that children build through their experiences inside and outside the early childhood education institution. With the aim of carrying out a study with the company of children, we opted for the ethnography as a methodological approach. Regarding the field research, we privileged a multi-grade class in early childhood education in a public educational institution, located in the rural context of the municipality of Guarapari/ES. As a strategy for the interpretation and recording of data, in addition to participant observation, conversations, games and moving around with children, we have used photographic records and field diaries. Analyzing the experiences lived by children, from the traces of their own culture, is a task needed to understand them and their childhoods. The analysis of children’s cultures, through its grammar, can constitute an important object to understand the social position that children build, through their cultures, a task that is to a large extent to be performed, considering the scarce amount of studies and publications so far.